Perspektif lmplementasi Total Quality Management (TQM) Pada lnstitusi Pendidikan Tinggi - Slamet, Slamet (ULUL ALBAB Jurnal Studi Islam, 2002)
Change of environment having the character of turbulen, bringing impact to institution management, not escape education, hence expected have to can alter orientation having the character of proaktif as influence of change of world recognized with globalization. Institution higher education represent mediator between society as society and input as service user or higher education. Therefore higher education have to pay attention importance of society as according to outcome with requirement of student, society and pay attention the quality of education with Total Quality Management (TQM) approach which during the time used many in the world of business. Reason of ht base is that education institution output will compete in labor market at free market which have been started 2003 year the, where society we will come in contact with world cleft people. Therefore require to be drawn up by human resource to anticipate the emulation, passing going concern process (improvement continous). TQM approach represent approach for the management to build a system which focusing to one who aim to to increase the quality of product (yealded jasa) on an on going basis to reach satisfaction of society. This system work by horizontal entangling all human resource, from top to bottom, extend from upstream to downstream, incluiding input link and of output and also customer.